2020
DOI: 10.1107/s2053273320009717
|View full text |Cite
|
Sign up to set email alerts
|

Pure discrete spectrum and regular model sets in d-dimensional unimodular substitution tilings

Abstract: Primitive substitution tilings on {\bb R}^d whose expansion maps are unimodular are considered. It is assumed that all the eigenvalues of the expansion maps are algebraic conjugates with the same multiplicity. In this case, a cut-and-project scheme can be constructed with a Euclidean internal space. Under some additional condition, it is shown that if the substitution tiling has pure discrete spectrum, then the corresponding representative point sets are regular model sets in that cut-and-project scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…showed that the nematic phase becomes ferroelectric when a rod‐shaped molecule has a large dipole moment that exceeds a certain critical magnitude along its long axis. [ 32,33 ] This theoretical prediction is supported by the fact that nematic liquid crystals of aromatic polyesters and helical polypeptides with a large dipole moment along their long axis form ferroelectric nematic (N F ) phases via dipole–dipole interaction. [ 34–36 ] Furthermore, more recent studies have indicated that low‐molecular‐weight liquid crystals with a dioxane group at the molecular end (referred to as DIO hereafter) exhibit a ferroelectric N F phase and that their relative dielectric constant exceeds 10 000.…”
Section: Introductionmentioning
confidence: 99%
“…showed that the nematic phase becomes ferroelectric when a rod‐shaped molecule has a large dipole moment that exceeds a certain critical magnitude along its long axis. [ 32,33 ] This theoretical prediction is supported by the fact that nematic liquid crystals of aromatic polyesters and helical polypeptides with a large dipole moment along their long axis form ferroelectric nematic (N F ) phases via dipole–dipole interaction. [ 34–36 ] Furthermore, more recent studies have indicated that low‐molecular‐weight liquid crystals with a dioxane group at the molecular end (referred to as DIO hereafter) exhibit a ferroelectric N F phase and that their relative dielectric constant exceeds 10 000.…”
Section: Introductionmentioning
confidence: 99%